New action plan to beat world hunger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
A new initiative to combat world hunger has been launched. The aim is to double food production in the next thirty years by paying more attention to the needs of the poorest farmers, without jeopardizing the environment. The initiative has come...